Biodisintegration of human mucin protein by protease produced from Escherichia coli AJ55 isolated from Urinary Tract Infection of Iraqi pa-tients - Alsa’ady, Ali J.; Ibrahim, Aida H.; Hassan, Haider A.; Abdulameer, Zainab W. (Iraqi Journal of Science, 2023)
Proteases have various applications in the food, pharmaceutical, medicine, pathogenicity of some pathogenic bacteria, and detergent sectors as well as meeting the needs of approximately 60% of the global enzyme industry, whereas they catalyze the breakdown of protein molecules into peptides and amino acids. Production and purification of protease enzyme by the isolate Escherichia coli AJ55 was scrutinized in the present study. Cultivation optimum conditions, were various complex medium, carbon source, nitrogen source, temperature, pH of the medium, and time of incubation were optimized to enhance the total protease production in shake flask culture of E.coli AJ55. The nutrient broth supplemented with 2% glucose and 2% yeast extract, with a pH of 7.0 and incubated at 37 °C for 24 hours, better conditioned for producing the maximum production of protease. Escherichia coli AJ55 proteolytic enzyme was separated and purified using ion-exchange chromatography on a DEAE-Cellulose column and Sephadex G-150 gel after being precipitated with 0-70% saturated ammonium sulfate. Protease that had been partially purified had a yield of 34%, a purification fold of 13.4, an activity of 12.16 U/ml, a protein concentration of 0.005 mg/ml, and a specific activity of 2432 U/mg. By using gel filtration chromatography on a Sephadex G-150 gel, partially purified protease was examined for its ability to cleave the mucin protein. The findings of mucin biodegradation showed that the five fractions of the small peptides were produced after treatment of mucin with partially purified protease.